MENGEMBANGKAN KARAKTER PESERTA DIDIK MELALUI PROSES PENDIDIKAN DI SMA NEGERI 2 SIPORA KABUPATEN KEPULAUAN MENTAWAI - Budi Juliardi; Ranti Nazmi; Lira Suryani (STKIP PGRI Sumatera Barat, 2020)
Character education is a must for countries that want to make their citizens have good attitudes and behaviors. The goal to be achieved in Community Service activities is to make students aware of the need to have and implement attitudes that have character. In the school environment, the teacher's role is to educate the character of students. Thus, community service activities want to make students aware and want to instill and develop character attitudes through socialization. Socialization is given to provide direct literacy of character education to students. Socialization is filled with questions and answers so that students who are not familiar with matters relating to character can immediately ask the implementation team.